Factors influencing Malaysian consumers online purchase of herbal products - Rezai, Golnaz; Mohd Zahran, Muhammad Zaid; Mohamed, Zainal Abidin; Sharifuddin, Juwaidah (Universiti Putra Malaysia Press, 2013)
The industry for natural products has experienced a significant growth in demand for its products and there is no surprise that the government has given it full support. The economical production methods have made it possible for the Malaysian Small and Medium Businesses Enterprises (SMEs) to increase their output. However due to the limited number of available resources, local SMEs are finding themselves in competition for shelf space in retail grocery stores. One way to resolve this issue is for producers and entrepreneurs to turn to the internet to attract customers. A website that could offer the herbal products online could be an ideal venue to market such products. Moreover, the launch of such a website needs relatively minimal skills and infrastructure. In this study 1063 internet users were interviewed online in order to identify the factors which could influence their intention to purchase herbal products online. Descriptive Analysis and Factor Analysis were employed in this study. The factors which have been found to be significant in predicting the intentions of an average Malaysian to shop online for herbal product are: the internet speed and experience, herbal product characteristics, perceived benefits, subjective norm, payment methods and English proficiency.